Seed bank in soil in Caatinga areas under ruminant grazing (Research, Society and Development, 2020)
The study of the seed bank in the soil makes it possible to monitor and understand the effects of animal interference on the dynamics of plant communities. The aim of this study was to know the floristic composition, the germination density and the diversity of the seed bank in the soil of Caatinga areas grazed by ruminant animals. Two grazing areas were selected, one with goats and the other with bovines, and 10 soil samples has been collected and the material distributed in plastic trays and daily irrigated. The seed density was determined by the plantlent emergence method and diversity was assessed using Shannon (H') and Pielou (J') indexes. The seed bank’s flora varied according to the grazing area, being represented by 28 species, 25 genera and 12 families, among them Fabaceae and Poaceae with the highest number of species. The predominant lift-form is herbaceous and the germination density is 1,033 and 740 seeds/m², in soils with goats and bovines, respectively. The area with grazing goats provides the highest diversity rates.